THE ARTISTIC AND AESTHETIC FOUNDATIONS OF THE CREATIVE COLLABORATION BETWEEN ALISHER NAVOI AND ABDURAHMAN JAMI - Kurbanaliyeva Makhfirat Sadullaevna (International Journal of Literature and Language Studies, 2026)
This article examines the artistic and aesthetic foundations of the creative collaboration between Alisher Navoi and Abdurahman Jami, two outstanding representatives of classical Eastern literature. Their relationship was not limited to personal friendship or the traditional bond between a teacher and a disciple. It developed into a productive intellectual and literary partnership based on shared spiritual values, humanistic ideals, Sufi philosophy, artistic principles, and mutual respect. The works of Navoi and Jami reveal common aesthetic views concerning the nature of poetry, the responsibility of the poet, the spiritual development of the individual, the relationship between divine and earthly love, and the moral function of literature.